2006
DOI: 10.1088/1748-6041/1/1/001
|View full text |Cite
|
Sign up to set email alerts
|

Human red blood cell deformed under thermal fluid flow

Abstract: The flow-induced mechanical deformation of a human red blood cell (RBC) during thermal transition between room temperature and 42.0 degrees C is interrogated by laser tweezer experiments. Based on the experimental geometry of the deformed RBC, the surface stresses are determined with the aid of computational fluid dynamics simulation. It is found that the RBC is more deformable while heating through 37.0 degrees C to 42.0 degrees C, especially at a higher flow velocity due to a thermal-fluid effect. More impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It is known for a long time that elastic membrane moduli are temperature dependent [71]. More recent investigation by laser tweezers on the relationships between the temperature and the biomechanical properties of human erythrocyte showed that the RBC is more deformable when heated above 37 • C under thermal fluid flow conditions, especially at a higher flow velocity due to a thermal-fluid effect [29] and possibly due to a temperature higher than T c for hemoglobin according to the above-mentioned findings. In a different system, Couette (concentric cylinders) shearing system, the EIs measured at temperature between 25-37 • C were not significantly different from each other, regardless of the shear stress; EIs were found to be different in lower range: 20-30 • C [5,61].…”
Section: Relation To the Temperaturementioning
confidence: 84%
“…It is known for a long time that elastic membrane moduli are temperature dependent [71]. More recent investigation by laser tweezers on the relationships between the temperature and the biomechanical properties of human erythrocyte showed that the RBC is more deformable when heated above 37 • C under thermal fluid flow conditions, especially at a higher flow velocity due to a thermal-fluid effect [29] and possibly due to a temperature higher than T c for hemoglobin according to the above-mentioned findings. In a different system, Couette (concentric cylinders) shearing system, the EIs measured at temperature between 25-37 • C were not significantly different from each other, regardless of the shear stress; EIs were found to be different in lower range: 20-30 • C [5,61].…”
Section: Relation To the Temperaturementioning
confidence: 84%
“…It has been found that the mechanical properties of RBCs can be changed due to temperature change in the human body (Waugh & Evans 1979). Foo et al (2006) investigated the effect of heating and cooling on mechanical properties of a single RBC trapped by OT. It was found that the extra deformation under hydrodynamic flow for an RBC at body temperature (378C) was significantly higher than that at room temperature.…”
Section: Mechanical Characterization Of Rbcsmentioning
confidence: 99%
“…Due to their surface properties, microstructure, degree of antigenicity of structural compounds, ability to absorb plasma proteins and overall porosity, biomaterials can directly influence the adhesion and differentiation processes of adaptive and innate immune cells. Macrophages are the dominant infiltrating cells which respond rapidly to biomaterial implantation in tissues [58,59]. These cells and their fused morphologic variants usually remain at biomaterial-tissue interfaces for the life-time of the device in vivo .…”
Section: Factors and Molecular Mechanisms Of The Ecm Bioactivity Durimentioning
confidence: 99%